Surviving the challenge: The crucial role of disruptive strategies in pandemic gastronomy - Salas Carrera, Martin (2024)
The present article analyses the crucial role of disruptive strategies in the survival and adaptation of the gastronomic industry during the COVID-19 pandemic. Through qualitative research based on in-depth interviews with entrepreneurs and gastronomic managers, expected trends and practices were identified, reflecting a proactive and adaptable approach to crisis management. The results revealed various innovative strategies, from personalised delivery services to product diversification and strategic collaboration with other establishments. Rapid adaptation to new market conditions, effective risk management, and active pursuit of strategic partnerships emerged as critical elements for business resilience. Additionally, digital transformation and effective customer communication were highlighted as determining factors for maintaining relevance and competitiveness in an ever-changing business environment.